Identification and removal of a cryptic impurity in pomalidomide-PEG based PROTAC - Wang, Bingnan; Lu, Yong; Chen, Chuo (Beilstein Journal of Organic Chemistry, 2025)
Chemically induced dimerization is a powerful tool for studying protein function, wherein the IMiD (the “immunomodulatory drug”) class of PROTAC molecules with a PEG linker is frequently used to promote targeted protein degradation. The standard protocol for their synthesis involves nucleophilic aromatic substitution of 4-fluorothalidomide with a PEG-amine. We report herein the identification of a commonly ignored impurity generated in this process. Nucleophilic acyl substitution competes with aromatic substitution to displace glutarimide and gives a byproduct that can co-elute with the desired product on HPLC throughout the remainder of the synthesis. Scavenging with taurine is a convenient way to minimize this contamination.
Keywords: glutarimide; IMiD; impurity; nucleophilic acyl substitution; PROTAC